Influence of localized magnetic field and strong viscosity on the biomagnetic fluid flow in a rectangular channel. (October 2017) - Siddiqa, Sadia; Begum, Naheed; Safdar, S.; Hossain, M.A.; Al-Rashed, Abdullah A.A.A.
Highlights: In this paper biomagnetic fluid flow in an enclosure of rectangular channel is considered. The flow is under the influence of applied magnetic field and temperature-dependent viscosity. An electrically conducting magnetic fluid (blood) is discussed which also exhibits magnetization. Solutions are obtained numerically by employing upwind scheme together with successive over relaxation. It is observed that the strength of the vortices and the temperature values increases by magnifying the magnetic intensity and circular contours are generated extensively for the fluid having variable viscosity. Graphical abstract: Abstract: In this paper biomagnetic fluid flow in a rectangular enclosure is studied under the influence of applied magnetic field and temperature-dependent viscosity. An electrically conducting magnetic fluid (blood) is considered here which also exhibits magnetization. It is assumed that the magnetization M ¯ of the fluid is varying linearly with temperature T ¯ and magnetic field intensity H ¯ . The viscosity μ ¯ of biofluid is taken to be an exponential function of temperature. The mathematical model for the present problem results in a nonlinear and coupled system of equations and is given in stream function-vorticity-temperature formulation for the purpose of numerical treatment. Solutions are obtained iteratively by employing upwind scheme together with successive over relaxation method. Numerical results are presented in terms of average Nusselt number, streamlines, isotherms and vorticity function contours indicating that presence of magnetic source and viscosity variations influences the flow field considerably. It is found that the strength of the vortices and the temperature increases by magnifying the magnetic intensity and circular contours are generated extensively for the blood having variable viscosity.